2023
DOI: 10.1021/acs.chemmater.3c01635
|View full text |Cite
|
Sign up to set email alerts
|

Cs3Bi2Br9/g-C3N4 Direct Z-Scheme Heterojunction for Enhanced Photocatalytic Reduction of CO2 to CO

Yasmine Baghdadi,
Filipp Temerov,
Junyi Cui
et al.

Abstract: Lead-free halide perovskite derivative Cs 3 Bi 2 Br 9 has recently been found to possess optoelectronic properties suitable for photocatalytic CO 2 reduction reactions to CO. However, further work needs to be performed to boost charge separation for improving the overall efficiency of the photocatalyst. This report demonstrates the synthesis of a hybrid inorganic/organic heterojunction between Cs 3 Bi 2 Br 9 and g-C 3 N 4 at different ratios, achieved by growing Cs 3 Bi 2 Br 9 crystals on the surface of g-C 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…5c and d), the crystals were hexagonal in shape with a lattice spacing of approximately 4.2 Å corresponding to the (102) plane and similar to previously reported values in the literature. 15,47 In contrast, TEM micrographs of BGCN (Fig. S3†) and 2EGCN (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…5c and d), the crystals were hexagonal in shape with a lattice spacing of approximately 4.2 Å corresponding to the (102) plane and similar to previously reported values in the literature. 15,47 In contrast, TEM micrographs of BGCN (Fig. S3†) and 2EGCN (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…45 The displayed peaks proved the crystalline nature of the semiconductor with peaks at 13.1, 16.1, 22.4, 27.2, 27.4, 31.9, 35.8, 39.4, and 45.5° (2 θ ) corresponding to the planes (100), (101), (102), (003), (201), (202), (212), and (220), respectively. 15,46 The addition of BGCN, EGCN, BGCN/rGO, and EGCN/rGO did not largely affect the crystalline structure of CBB. However, taking a closer look at the region between 26 and 28.5° (2 θ ) where the (003) and (201) peaks of CBB coincide with the (002) peak of GCN, a deconvolution showed that the ratio of the CBB peaks had changed suggesting a suppressed preferential growth in the presence of a secondary material during the synthesis (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Inspired by biomimetic artificial photosynthesis, the concept of Z-scheme photocatalytic systems was first proposed by Bard in 1979 . Despite having the same band structure configuration as a Type-II heterojunction, the Z-scheme heterojunction has a distinctly different charge-transfer mechanism, following an exclusive Z-shape charge carrier pathway (Figure d) to promote electron–hole pair separation. ,,, There are different types of Z-scheme heterojunctions, and their detailed respective working principles are available from various literature reports. ,, Notably, the direct Z-scheme heterojunction has been extensively investigated in photocatalysis, especially in CO 2 photoreduction of high energy demand, owing to the well-preserved redox ability of each constituent in the composite in addition to the spatially separation of reduction and oxidation sites. ,,, Typically, the LFHPs are utilized as the reduction site by hybridization with a semiconductor with lower lying CB and VB. As a prevalent Bi-based oxidation photocatalyst, i.e., Bi 2 WO 6 , has been investigated for Z-scheme heterostructure formation with LFHPs such as Cs 3 Bi 2 Br 9 , Cs 3 Bi 2 I 9 , and Cs 2 AgBiBr 6 , in which all these Bi-based Z-scheme heterojunction architectures were shown to exhibit better photocatalytic CO 2 reduction performance.…”
Section: Strategies For Application and Modification Of Lfhp-based Ph...mentioning
confidence: 99%